Fibrinogen Metabolism in Healthy Dogs and in Dogs with CCI4-Induced Liver Damage and with Portal Vein Occlusion - Tytgat, G. N.; Collen, D.; Oei, L. S.; Van Damme, B. (Thrombosis and Haemostasis, 1972)
The metabolism of dog fibrinogen, labelled with radioactive iodine was studied in 16 healthy dogs on 28 occasions, in 12 dogs with CCl4-induced chronic liver damage and in 5 dogs with interruption of the hepatoportal blood flow by occlusion of the portal vein.Results in healthy control dogs were: plasma volume 48±12 ml/kg ; plasma fibrinogen concentration 316±102 mg%; total plasma fibrinogen pool 168±42 mg/kg, representing 0.72±0.08 of the total body pool; fibrinogen half-life 2.54±0.23 day; fractional catabolic rate 0.39±0.05 of the plasma pool per day; absolute catabolic rate 58±25 mg/kg per day.Results in dogs with CCl4-induced liver damage were: plasma volume 46 ± 12 ml/kg ; plasma fibrinogen concentration 334±97 mg%; total plasma fibrinogen pool 152±55 mg/kg, representing 0.70±0.04 of the total body pool; fibrinogen half-life 2.15±0.26 days; fractional catabolic rate 0.47±0.06 of the plasma pool per day; absolute catabolic rate 71±21 mg/kg per day.Results in dogs with longstanding portal vein occlusion were: plasma volume 41 ±8 ml/kg; plasma fibrinogen concentration 330±23 mg%; total plasma fibrinogen pool 142±36 mg/kg, representing 0.70±0.06 of the total body pool; fibrinogen half-life 2.60 ±0.36 days; fractional catabolic rate 0.40 ±0.04 of the plasma pool per day; absolute catabolic rate 56±14 mg/kg per day.A significant difference between control dogs and dogs with liver disease was observed for the fibrinogen half-life and the fractional catabolic rate. All fibrinogen turnover data in dogs with portal vein occlusion were comparable to control values.Heparinization did not influence the fibrinogen half-life in most of the control dogs and in the dogs with portal vein occlusion ; however in 2 control dogs, a prolongation of their rather short fibrinogen survival occurred during anticoagulation. In contrast, a general trend towards prolongation and occasionally normalization of the fibrinogen life span during heparinization was observed in the dogs with liver damage, supporting the concept of accelerated fibrinogen consumption by a process of disseminated intravascular coagulation in liver disease.